Phytochemicals from Calophyllum canum Hook f. ex T. Anderson and their neuroprotective effects - Pin Fen, Chua; Mas Atikah, Lizazman; Vivien Mian Jong, Yii; William K., Lim; Thiruventhan, Karunakaran (Taylor & Francis, 2022)
Previous phytochemical investigations reported that Calophyllum spp have biosynthesized a wide range of bioactive phenolics such as xanthones and coumarins. The phytochemical study conducted on the stem bark of C. canum has led to the isolation of eight trioxygenated xanthones namely: 5-methoxytrapezifolixanthone (1), 5-methoxyananixanthone (2), caloxanthone C (3), 1,5-dihydroxy-3-methoxy-4-isoprenylxanthone (4), 6-deoxyisojacareubin (5), euxanthone (6), trapezifolixanthone (7), ananixanthone (8), together with three common triterpenoids, β-sitosterol (9), friedelin (10), and stigmasterol (11). Furthermore, xanthones 1 and 2 were isolated for the first time as naturally occurring xanthones from the plant extract. The structures of these compounds were identified and elucidated using advanced spectroscopic techniques such as 1 D & 2 D NMR, MS, and FTIR. The neuroprotective property of selected compounds was tested through in vitro stroke model. Among all tested compounds, 1 µm of compounds 8, 9, and 10 showed significant neuroprotective activity via reduction of apoptosis by ∼ 50%.